2017
DOI: 10.1038/s41598-017-16879-0
|View full text |Cite
|
Sign up to set email alerts
|

Coupling optogenetics and light-sheet microscopy, a method to study Wnt signaling during embryogenesis

Abstract: Optogenetics allows precise, fast and reversible intervention in biological processes. Light-sheet microscopy allows observation of the full course of Drosophila embryonic development from egg to larva. Bringing the two approaches together allows unparalleled precision into the temporal regulation of signaling pathways and cellular processes in vivo. To develop this method, we investigated the regulation of canonical Wnt signaling during anterior-posterior patterning of the Drosophila embryonic epidermis. Cryp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Yang et al (2014), found that optogenetic activation of VM astrocytes can enhance the DAergic differentiation of stem cells and promote brain repair in PD models in vivo and in vitro, very likely via the mediation of WβC activation. Kaur et al (2017) addressed the potential of coupling optogenetics and light-sheet microscopy to study Wnt signalling during embryogenesis, showing that WβC-signalling is required not only for Drosophila pattern formation, but also for maintenance later in development. Additionally, Zhang, Huang, et al (2016c) Ameliorates cognitive function, enhances neurogenesis, mitigates inflammation and mitochondrial dysfunction in hippocampus in a rodent model of gulf war illeness; WβC-AC involvement to be elucidated Kodali et al (2018) Exercise, environmental enrichment…”
Section: Optogeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al (2014), found that optogenetic activation of VM astrocytes can enhance the DAergic differentiation of stem cells and promote brain repair in PD models in vivo and in vitro, very likely via the mediation of WβC activation. Kaur et al (2017) addressed the potential of coupling optogenetics and light-sheet microscopy to study Wnt signalling during embryogenesis, showing that WβC-signalling is required not only for Drosophila pattern formation, but also for maintenance later in development. Additionally, Zhang, Huang, et al (2016c) Ameliorates cognitive function, enhances neurogenesis, mitigates inflammation and mitochondrial dysfunction in hippocampus in a rodent model of gulf war illeness; WβC-AC involvement to be elucidated Kodali et al (2018) Exercise, environmental enrichment…”
Section: Optogeneticsmentioning
confidence: 99%
“…Optogenetic activation of VM astrocytes enhances DAergic differentiation of NSCs and promotes brain repair in PD rodent models; WβC-AC involvement to be elucidated Yang et al (2014) Optical depolarization of DCX-expressing neuroblasts promotes cognitive recovery and maturation of newborn neurons after traumatic brain injury via WβC-AC Zhang, Huang, et al (2016c) Coupling of optogenetics and light-sheet microscopy reveals WβC-AC during embryogenesis and post-natal development Kaur et al (2017) WβC-AC can be controlled in vivo via light responsive capsules. Ambrosone et al (2016) Optical depolarization promoted the maturation of neural stem cells via WβC-AC Xia et al (2014) (Continues)…”
Section: Optogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the moment, studying self‐organization with in toto imaging during development is performed on embryonic bodies , gastruloids , organoids or small‐scale animals. Whole animals such as Hydra or C. elegans can be imaged during their entire development, while larger organisms such as D. rerio or D. melanogaster provide fundamental insights into embryonic development. These model systems are highly informative for studying evolutionary conserved mechanisms, despite limitations in their multicellular complexity and tissue functionality.…”
Section: Scale‐crossing Technologiesmentioning
confidence: 99%
“…Additionally, modern imaging methods such as light-sheet microscopy and confocal microscopy allow for precise in vivo observation. These, when combined with optogenetic approaches perturbing signal transduction pathways, could translate into an in vivo 2i system, where pathways could be turned on or off and the effects could be imaged [ 68 , 69 , 70 , 71 , 72 ]. In mice, pluripotency factors have been demonstrated to be functionally redundant; therefore, given the relative difficulty of manipulating mice genetically, Drosophila may be an effective system to dissect the individual influences of each gene more carefully as related to Wnt signaling [ 38 , 73 ].…”
Section: Benefits Of Using Drosophila As a Modementioning
confidence: 99%